Competence, Compassion, and Care of the Self: Family Caregiving Needs and Concerns in Heart Failure. Issue 3 (May 2016) - Sullivan, Barbara-Jean; Marcuccilli, Linda; Sloan, Rebecca; Gradus-Pizlo, Irmina; Bakas, Tamilyn; Jung, Miyeon; Pressler, Susan J.
Abstract : Background: Family caregivers are essential to the well-being of patients with chronic heart failure (HF) because they provide care in managing complex medication regimens, dietary sodium restrictions, and symptoms. Objective: The purpose of this qualitative study was to gain a deeper understanding of the HF caregiving experience and describe the needs and concerns expressed by caregivers. Methods: Qualitative descriptive methodology was conducted using data from responses to open-ended questions asked as part of a larger longitudinal study. The sample was 63 patients with HF and 63 family caregivers. Results: Using basic content analysis, the 3 main themes of needs and concerns that emerged were competence concerns, compassion maintenance, and care of the self. Subthemes of competence concerns were doing things right, making a serious mistake, and uncertainty. Conclusions: Family caregivers of patients with HF had many needs and concerns about their competence in performing tasks, their compassion, and caring for themselves. Data can be used to design testable interventions to improve the HF caregiving experience for patients and caregivers.